Monteverdi - Fabbri, Paolo -1948 (Turin EDT/Musica, 1985)
Monteverdi's contribution to secular, sacred and theatrical music in the period was unparalleled: his madrigals, church music and operas remain very much alive today. A large number of contemporary documents, including some 130 of his own letters, offer rich insights into the composer and his times, also illuminating the many and varied contexts for music making in the most important musical centres in Italy. Fabbri uses these documents and other sources to present a rich narrative focusing on a composer who has perhaps rightly been called the 'father of modern music'. This translation brings an indispensable text to a much broader readership, providing a vivid picture of a fascinating period in music history.
Bibliography: p. 439-446.
Keywords: Monteverdi, Claudio -- 1567-1643; Composer; Biography; Italy